Group-centered prevention in mental health : theory, training, and practice - Harpine, Elaine Clanton (Unites States of America : Springer, 2015)
This book presents the concept of group-centered prevention and provides explanations and exercises for learning the method and teaching it to others. Detailed studies offer evidence for the continuing importance of prevention in mental well-being and distinguishes group-centered prevention from other group interventions by its ability to resolve incipient mental health issues and emotional problems. Case examples with adults, children, couples, and others demonstrate successful uses of group-centered techniques as well as illustrate the problems that arise in group settings. The book's ready-to-apply training exercises give prospective group leaders practice in starting new groups, fostering cohesion, integrating therapeutic factors into sessions, and other core skills. Featured topics include: Group-centered prevention in contrast with other group interventions.
1. What is group-centered prevention? -- 2. What is the role of group dynamics in group prevention? -- 3.Why is group process important in group prevention? -- 4. How can a group best achieve cohesive group interaction? -- 5. Are prevention groups therapeutic? -- 6. Is intrinsic motivation better than extrinsic motivation? -- 7. Is self-efficacy more important than self-esteem? -- 8. Are there stages of development with a new group? -- 9. What kind of training does a group-centered preventionist need? .
Includes bibliographical references and index.
Keywords: CHILD DEVELOPMENT